Computing C-space entropy for view planning based on beam sensor model - Wang, P.; Gupta, K. (Proceedings 2002 IEEE/RSJ International Conference on Intelligent Robots and Systems : September 30-October 4, EPFL Lausanne, Switzerland, 2002)
The concept of C-space entropy was recently introduced by the authors (2000, 2001), as a measure of knowledge of C-space for sensor-based path planning and exploration for general robot-sensor systems. The robot plans the next sensing action to maximally reduce the expected C-space entropy, also called the maximal expected entropy reduction, or MER criterion. The expected C-space entropy computation, however, made two idealized assumptions. The first was that the sensor field of view (FOV) is a point; and the second was that no visibility (or occlusion) constraints are taken into account, i.e., as if the obstacles are transparent. We extend the expected C-space entropy formulation where the sensor FOV is a beam and furthermore, it is subject to visibility constraints, as is the case with real range sensors. Planar simulations show that this new formulation results in more efficient exploration.